Likeness - French, Tana (New York : Penguin Books, 2009)
Six months after the events of In the Woods, Detective Cassie Maddox is still trying to recover. She's transferred out of the murder squad and started a relationship with Detective Sam O'Neill, but she's too badly shaken to make a commitment to him or to her career. Then Sam calls her to the scene of his new case: a young woman found stabbed to death in a small town outside Dublin. The dead girl's ID says her name is Lexie Madison--the identity Cassie used years ago as an undercover detective--and she looks exactly like Cassie--From publisher description.
"First published in the United States of America by Viking Penguin ... 2008." -- T.p. verso.
Keywords: Women detectives -- Ireland; Murder -- Investigation; Mystery fiction